Photography and Videography Training as Branding Media at SMKN 12 Malang - Kabelen, Nicholaus Wayong; Habibi, Azwar Riza; Sapoetra, Yudistira Arya; Hakim, Lukman (Institut Teknologi dan Bisnis Asia Malang, 2025)
Purpose: This community service activity aims to enhance the videography skills of students at SMKN 12 Malang, particularly in product video shooting and editing. This training is expected to support product promotion through creative and engaging video media. Method: The training included an introduction to basic videography techniques such as lighting, angles and shooting settings. Students were trained to use video editing applications such as CapCut to add visual effects, transitions, audio, as well as compiling video-based product e-catalogs. An evaluation was conducted using a questionnaire to measure participants' satisfaction with the training. Practical Application: Students who take part in this training are expected to be able to produce creative and quality product promotion videos. This ability is relevant to support the promotional needs of local products and the creative industry in general. Conclusion: The training received a positive response from the participants, with 88% feeling satisfied and showing high enthusiasm, as seen from their improvisation and creativity in producing videos. This activity is expected to provide long-term benefits in developing students' videography skills to support the needs of the creative industry.